Reducing the Effectiveness of Gray-Hole Attack in Manet - Ancy Breen, W; Durga Devi, S; Sushmitha, E; Suveetha, V (International Journal of Engineering and Technology, 2018)
MANET is the mobile ad-hoc network. Security is very important especially when transmitting the data packets from one node to another. MANET is constructed by grouping mobile wireless nodes with no fixed infrastructure. In order to forward the packets, all the nodes in the network must cooperate with each other, so that the nodes beyond the radio ranges can communicate. Each node acts as a router and MANET is infrastructure-less networks. Hence, MANET is open to more security attacks such as Gray-hole attack, Black-hole attack and worm-hole attack. Due to the dynamism in network topology, MANETS are highly vulnerable and are prone to malicious attack. Security issue is highly challenging in MANET. Understanding the different form of possible attacks and providing good security solutions is important for secure data transmission between nodes. The most dangerous attack among these attacks is Gray-hole attack. In this paper, it proposed a method for reducing the Gray-hole attack. Our proposed algorithm MAODV identifies the malicious node before the data transmission process and it greatly reduces the dropping of data packets.